The Science of Adapted Throws: A Systematic Search and Narrative Evidence Synthesis - Farias-Valenzuela, C (Frontiers Media SA, 2025)
Introduction: Paralympic throwing events have grown rapidly, yet the scientific evidence guiding technique, training and classification remains fragmented across biomechanics, physiology and psychosocial domains. Objective: To provide an evidence-based overview of adapted throws by comprehensively examining the peer-reviewed literature. Methods: A systematic search of PubMed, Scopus, and Web of Science (inception—Feb 2025) using the terms Paralympic OR adapted OR disability AND throw AND (shot OR discus OR javelin OR club). Inclusion criteria comprised: (i) Athletes with physical impairments who participate in Para Athletics throwing events, (ii) Non-disabled individuals studied in research explicitly designed to inform or understand Para Athletics throwing techniques. Data were synthesized narratively and clustered by study theme. Results: Nineteen studies (n = 345 para athletes; 14 sport classes) met the criteria. Biomechanical analyses identified release velocity (8.3–10.0 m·s−1 in F52–F55 shot put) and optimal angles (27.5°–37°) as key performance determinants. Assistive devices improved results by 8% in F32 athletes. Significant research gaps exist for visual impairment (F11–F13), intellectual impairment (F20), and prosthesis-user classes (F61–F64). Conclusion: While class-specific technical models are emerging, particularly for seated throwers, 38% of throwing classifications lack published research. Future studies should prioritize underrepresented classes and develop standardized assessment protocols. 2025 Garcia-Carrillo, Lasso-Quilindo, Chalapud-Narváez, Castillo-Paredes, Farías-Valenzuela, Alarcón-Rivera, Yáñez-Sepúlveda and Judge.